Issue-Based Citizenship Learning through Indonesian Argumentative Texts: Its Impact on Students' Civic Reasoning and Writing Skills - A. Rizal; Andi Hamsiah; Andi Agusniati (JPI: Jurnal Pustaka Indonesia, 2026)
This study examines the impact of citizenship issue-based learning through Indonesian argumentative texts on students' civic reasoning and writing skills at senior secondary schools in Bone Regency. Employing a convergent mixed-methods design, the study involved 210 Grade 11 students from three schools (SMAN 9 Bone, SMAN 6 Bone, and SMAN 11 Bone) and 12 Pancasila and Civic Education (PPKn) and Indonesian language teachers selected through purposive sampling. Quantitative data were gathered via a Civic Reasoning Test and an Argumentative Writing Assessment Rubric, while qualitative data were obtained through semi-structured interviews and classroom observations. Descriptive analysis revealed significant improvements in students' civic reasoning scores (mean increased from 61.3 to 78.6) and argumentative writing skills (mean increased from 63.8 to 80.2) following the issue-based learning intervention. Qualitative findings disclosed that the integration of contextually relevant citizenship issues into argumentative text production fostered critical thinking, evidence analysis, and responsible civic expression. Teachers identified time constraints and curriculum alignment as primary challenges while acknowledging marked increases in lesson relevance and student motivation. This study recommends the systematic integration of issue-based learning into PPKn and Indonesian language curricula as a contextual and literacy-grounded civic education strategy.